COMMUNITY-PRIVATE PARTNERSHIP (CPP) IN COMMUNITY BASED TOURISM MANAGEMENT: CASE STUDY OF BLANGSINGA VILLAGE, BALI - Sawitri, I Made Yaya; Prabawa, Made Suryanatha (Jurnal Widya Publika, 2022)
As an alternative form of tourism, Community-based Tourism (CBT) is expected to meet the social, environmental and economic needs of local communities through the offering of tourism products. CBT has enormous potential to be developed especially with the rising trend for an authentic and environmentally conscious travel experience. However, most CBT has very limited resources and knowledge to gain market access which lead to low competitiveness of its operation. This paper argues that one solution to advance community-owned tourism is by encouraging direct partnership between the Community and the private actor (investor) or the Community-Private Partnership (CPP). By using study case from Blangsinga tourism village, this research investigates how the partnership develop and how it can help the growth of the CBT. Qualitative methods, such as in-depth interview and participant observation, were employed. Examination on the operation showed that the partnership does not compromise the community’s ownership of the CBT. Instead, the involvement of the external parties is directed towards providing resources and knowledge for the development of the community.